The regulation of public debt: in the experiences of developed and developing countries - Ashurakhunov , Abdufattokh (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
The research paper examines the regulation of public debt and its essence as well as analyze the experience of countries which are developed and developing. In today's world, many countries borrow a large amount of debt in order to boost their economy and improve the living standards of its residents from financial organization or developed countries. Besides after getting financed, they have many problems and sufferings how to allocate that money properly and purposely, subsequently they cannot pay back the debt and its interest. In the worst case, that countries may collapse by putting more debt strain to themselves and suffer from getting revenue from the debt, pay back it to organizations and countries. These challenges may sometimes make it difficult for countries to maintain constant and sustainable economic growth. In this statement, we determine the primary factors and causes of the debt risk in how to manage them effectively as well as provide with strategies and methods in terms of government debt in the case of developed and developing countries. It addresses the different kinds of risks that may eventually pose a threat to the explosion of public debt. The utmost goal is to explain the reason behind the government borrowing money with the lowest rate of interest and sustaining fiscal stability.